A Share of VAT on GDP in Nepal After 2010 A.D - Adhikari, Krishna Gopal (Dristikon: A Multidisciplinary Journal, 2019)
This research paper examines the share of VAT on GDP in Nepal After 2010 A.D. Value Added Tax (VAT) is the most recent innovation in the field of taxation. Actually, VAT is considered one of the most important tax revenue of the second half of the twentieth century. It is a scientific tax system, which was first introduced in 1954 in France. VAT is a family member of indirect tax. Economic development has been one of the most popular slogans in almost all the developing countries all over the world. The main concern of study is to analyze the share of VAT on the gross domestic product in Nepal. This article based up secondary source of information collects from economic survey, books, article, journals and research paper. This paper employs descriptive research design. This study shows that the share of VAT is increasing every year since 2010 A.D. It plays the important role for economic development in Nepal. This article is very useful to the researchers, government and policy makers who want to know the contribution of VAT on GDP in Nepal. VAT is a broad based tax as it also covers the value added to each commodity by a firm during all stages of production and distribution.